High temperature liquid chromatography of tocol-derivatives on polybutadiene-coated zirconia stationary phases - Sanagi, Marsin Marsin (Springer Verlag, 2005)
High temperature reversed-phase high performance liquid chromatography is evaluated as a new approach for the separation of vitamin E isomers (a-, ?-, d-tocopherol, and a-, ?-, d-tocotrienol) and a-tocopherol acetate. The separations of each analyte were examined by varying the eluent composition and column temperature. Using a polybutadiene-coated zirconia column at temperatures of 80°C-140°C, complete separations were achieved within 10-20 min using organic modifier (acetonitrile) in the range of 40-50%. Irregularity of the Van't Hoff analysis was noted over the temperature studied. The plot tends to deviate from linearity at higher operating temperatures (140°C and 150°C) with linear deviation errors of 12.7% and 41.6%, respectively, for the mobile phase examined.